Hubungan Pemberian Makanan Pendamping ASI (MP-ASI) Dengan Status Gizi Pada Bayi Usia 6-24 Bulan - Wahyuni, Sri; Fatmayanti, Aulia; Ulfiana, Elisa; Primadasa, Nia (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2024)
Factors that influence the nutritional status of children under 2 years of age are the types ofadditional food or MP-ASI that are not appropriate and do not meet their needs. The Blora Regency HealthOffice noted that the prevalence of toddlers in the category of malnutrition and severe malnutrition in 2022increased when compared to 2020 and 2021, namely from 10.96% to 12.14% and 12.32% in 2023. Thepurpose of this study was to determine the relationship between the provision of complementary foods (MP-ASI) and nutritional status in infants aged 6-24 months in the Ngawen Health Center area, Blora Regencyin 2024. This type of research uses a cross-sectional approach. The population of all toddlers in the NgawenHealth Center working area is 89 children, with samples selected using purposive sampling techniquesobtained 73 respondents. The results of the univariate test showed that the provision of MP-ASI was mostlymixed (45.2%) and the nutritional status of the majority was good nutrition (61.6%). The results of thebivariate test showed that there was a relationship between the provision of complementary foods (MP-ASI) and nutritional status in infants aged 6-24 months in the Ngawen Health Center area, Blora Regencyin 2024 (chi square test value Ï = 0.013 <0.05). The results of this study are expected to help mothersprovide appropriate and correct complementary feeding according to their child's age so that theirdevelopment is better and they get a balanced nutritional intake